Peptide receptor radionuclide therapy in advanced Pheochromocytomas and Paragangliomas: a systematic review and meta-analysis - Su, Dan; Yang, Hongyu; Qiu, Chen; Chen, Yue (Frontiers in Oncology, 2023)
Objective: Peptide receptor radionuclide therapy (PRRT) for advanced pheochromocytomas and paragangliomas (PPGLs) has received increasing attention. The purpose of this article is to evaluate the efficacy and safety of PRRT in patients with metastatic or inoperable PPGLs by meta-analysis. Methods: A literature search was conducted in PubMed, Embase, Scopus, and Cochrane Library databases up to November 2022. All articles on PRRT for PPGLs were searched, and appropriate data were included for analysis. The measures evaluated included objective response rate (ORR), disease control rate (DCR), clinical response rate, biochemical response rate, progression-free survival (PFS), overall survival (OS), and adverse events. Statistical analysis was performed using Stata 16.0 and the R programming language, data were combined using a random-effects model, and the results were presented using forest plots. Results: A total of 20 studies with 330 patients were included in the analysis. The results showed that ORR and DCR were 20.0% (95% CI: 12.0%-28.0%) and 90.0% (95% CI: 85.0%-95.0%), respectively. Clinical and biochemical responses were 74.9% (95% CI: 56.3%-90.2%) and 69.5% (95%CI: 40.2%-92.9%). Median PFS and median OS were 31.79 (95% CI:21.25-42.33) months and 74.30 (95% CI: 0.75-147.84) months, respectively. Any grade of hematotoxicity and nephrotoxicity occurred in 22.3% (95% CI:12.5%-33.5%) and 4.3% (95% CI:0.2%-11.4%) patients. Grade 3-4 haemotoxicity occurred in 4.3% (95% CI:0.2%-11.4%) and grade 3-4 nephrotoxicity in 4/212 patients. Additionally, Treatment was discontinued in 9.0% (95% CI: 0.5%-23.3%) patients and one patient died as a result of a toxicity. Conclusions: Patients with metastatic or inoperable PPGLs can be effectively treated with PRRT, and it has a favorable safety profile.